2013
DOI: 10.1007/s11418-013-0809-5
|View full text |Cite
|
Sign up to set email alerts
|

Distinct intraspecific variations of garlic (Allium sativum L.) revealed by the exon–intron sequences of the alliinase gene

Abstract: Garlic (Allium sativum L.) has been used worldwide as a food and for medicinal purposes since early times. Garlic cultivars exhibit considerable morphological diversity despite the fact that they are mostly sterile and are grown only by vegetative propagation of cloves. Considerable recombination occurs in garlic genomes, including the genes involved in secondary metabolites. We examined the genomic DNAs (gDNAs) from garlic, encoding alliinase, a key enzyme involved in organosulfur metabolism in Allium plants.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The nuclear genome of Allium plants, such as garlic and onion, is relatively large (approximately 15 000 Mbp) compared with that of other monocot plants (Ohri and Pistrick , Endo et al. ,). Due to the limited genome information available for garlic, AFLP, ISSR and SSR markers are most applicable to analysis of garlic diversity.…”
mentioning
confidence: 99%
“…The nuclear genome of Allium plants, such as garlic and onion, is relatively large (approximately 15 000 Mbp) compared with that of other monocot plants (Ohri and Pistrick , Endo et al. ,). Due to the limited genome information available for garlic, AFLP, ISSR and SSR markers are most applicable to analysis of garlic diversity.…”
mentioning
confidence: 99%
“…Systematic reviews and recent studies provide evidence that garlic intake exhibited no significant effect on blood level of cholesterol [26,27]. The heterogenicity of the results are partly due to the variety of garlic preparations used, poor standardization of products tested, the diversity of study designs employed and/or not publishing little effects or no effects observed [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Jovan, which we investigated in more detail. Because previous studies have not focused on the first exon of the alliinase gene [ 24 , 25 ], we compared our sequences to complete sequences available in databases. Only the first ATG of sequence [GenBank: Z12622], which was used as a reference, was located in the same position as in our sequences.…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be expected for a protein with high substrate specificity participating in a catalytic process. Endo et al [ 24 ] reported that only functional copies of this gene occur in analysed genotypes garlics, probably reflecting the use of commercial garlic samples with fully functional enzymes to ensure the metabolism of flavor precursors. They also found the exon sequences highly conserved among all the clones studied.…”
Section: Discussionmentioning
confidence: 99%